Формирование функциональной грамотности на уроках математики как необходимый результат обучения современного школьника - Савкина, Е. В. (My University, 2016)
415 Methods : analysis of literature, drafting and application of test tasks taking into account principles "fundamental mathematical ideas", "mathematical competence", supervision. Methods : analysis of literature, drafting and application of test tasks taking into account principles "fundamental mathematical ideas", "mathematical competence", supervision. Result:forming of functional grammar correctness of children. Conclusions: Attracting in of intersubject information in the process of decision tasks of type PISA assists the deeper and intelligent mastering of programmatic material, children acquire and perfect practical abilities to expose cause and effect connections between the phenomena, processes. To create terms are thus created for the intelligent understanding of facts, theory, laws, specifications early the purchased knowledge on physics, chemistry, biology, ecology
Keywords: functional grammar correctness; independent educational activity; development of the critical thinking; competence- oriented personality